A Global Analysis of Kinase Function in Candida albicans Hyphal Morphogenesis Reveals a Role for the Endocytosis Regulator Akl1 - Hagit Bar-Yosef; Tsvia Gildor; Bernardo Ramírez-Zavala; Christian Schmauch; Ziva Weissman; Mariel Pinsky; Rawi Naddaf; Joachim Morschhäuser; Robert A. Arkowitz; Daniel Kornitzer (Frontiers in Cellular and Infection Microbiology, 2018)
The human pathogenic fungus Candida albicans can switch between yeast and hyphal morphologies as a function of environmental conditions and cellular physiology. The yeast-to-hyphae morphogenetic switch is activated by well-established, kinase-based signal transduction pathways that are induced by extracellular stimuli. In order to identify possible inhibitory pathways of the yeast-to-hyphae transition, we interrogated a collection of C. albicans protein kinases and phosphatases ectopically expressed under the regulation of the TETon promoter. Proportionately more phosphatases than kinases were identified that inhibited hyphal morphogenesis, consistent with the known role of protein phosphorylation in hyphal induction. Among the kinases, we identified AKL1 as a gene that significantly suppressed hyphal morphogenesis in serum. Akl1 specifically affected hyphal elongation rather than initiation: overexpression of AKL1 repressed hyphal growth, and deletion of AKL1 resulted in acceleration of the rate of hyphal elongation. Akl1 suppressed fluid-phase endocytosis, probably via Pan1, a putative clathrin-mediated endocytosis scaffolding protein. In the absence of Akl1, the Pan1 patches were delocalized from the sub-apical region, and fluid-phase endocytosis was intensified. These results underscore the requirement of an active endocytic pathway for hyphal morphogenesis. Furthermore, these results suggest that under standard conditions, endocytosis is rate-limiting for hyphal elongation.